Spektrum Epistemologi Kritik Hadis Kontemporer: Analisis Komparatif Metodologi Takhrīj al-Hadis al-Albani dan Muqbil bin Hadi al-Wadi‘i - Tofan Rinaldi; Muhammad Jadid Khadavi (Moral : Jurnal kajian Pendidikan Islam, 2026)
The study of takhrij al-hadith plays a crucial role in hadith scholarship, involving the tracing of transmission sources and evaluating the authenticity of sanad and matn through systematic analysis. In contemporary studies, differences in scholars’ approaches have led to variations in hadith classification and epistemological orientation. However, comparative research examining methodological criticism, epistemological foundations, and operational procedures of modern takhrij remains limited. This study aims to critically compare the methodologies of Muḥammad Nāṣiruddīn al-Albānī and Muqbil bin Hādī al-Wādiʿī, focusing on their evaluation of sanad and matn. Using a qualitative approach with an integrative literature review, this research analyzes primary works and relevant academic sources. The findings reveal three main epistemological patterns: independent reasoning through cross-narration, methodological caution based on classical authority, and a shared reliance on jarḥ wa taʿdīl. These differences influence hadith classification and reflect varying depths of criticism. The study shows that contemporary hadith criticism forms an epistemological spectrum rather than a strict methodological divide. It also highlights implications for religious practices, including the Megengan tradition in Java, which adapts to socio-economic contexts, and enriches comparative studies in hadith methodology.